Diagnostic reference levels for paediatric CT in Jordan. (6th November 2019) - Rawashdeh, Mohammad; Abdelrahman, Mostafa; Zaitoun, Maha; Saade, Charbel; Alewaidat, Haytham; McEntee, Mark F
Abstract: This study aimed to investigate the current status of Diagnostic Reference Levels (DRLs) in paediatric CT across Jordan. The dose data for four main CT examinations (brain, chest, abdominopelvic, and chest, abdomen and pelvis (CAP)) in hospitals and imaging centres (n = 4) were measured. The volume CT dose index (CTDIvol ) and Dose Length Product (DLP) values were compared within the different hospitals and age groups (<1 year, 1–4 years, 5–10 years and 11–18 years). DRLs in Jordan were compared to international DRLs. The paediatric population consisted of 1818 children; 61.4% of them were male. There were significant variations between the DRLs for each CT scanner with an up to four-fold difference in dose between hospitals. There were apparent significant differences between Jordan and other countries with the DLPs in Jordan being relatively high. However, for CTDIvol, the values in Jordan were close to those of other countries. This study confirmed variations in the CTDIvol and DLP values of paediatric CT scans in Jordan. These variations were attributed to the different protocols and equipment used. There is a need to optimise paediatric CT examinations doses in Jordan.